ANALISIS RISIKO USAHA BUDIDAYA IKAN LELE DUMBO DI KECAMATAN KOTA GAJAH KABUPATEN LAMPUNG TENGAH - Neni Marlina; Ktut Murniati; Eka Kasymir (Lampung University, 2021)
This research aims to determine the level of risk and behavior faced by farmers in dumbo catfish farming. This research was a survey conducted in Kota Gajah Subdistrict of Central Lampung Regency in August-September 2018. Respondents are 44 dumbo catfish farmers members of the Fish Cultivation Group (pokdakan) taken using simple random sampling. The results of this research showed that the dumbo catfish farming in Kota Gajah Subdistrict of Central Lampung Regency has the CV value price risk of 0.04 and the lower limit (L) of IDR15,320. The CV value less than 0.50 means that farmers risk suffered losses due to changes in low classified price. CV value of production risk is 0.04 and the lower limit (L) is 2,449.33 kg. The CV value less than 0.50 means that farmers risk experiencing losses due to changes in production relatively low. Based on the analysis that was done with the quadratic utility approach shows that dumbo catfish farmers in Kota Gajah Subdistrict are 41 farmers behave neutrally and 3 farmers behave boldly in facing the risk of catfish farming.Key words: behavior, dumbo catfish, farmers, risk